[1 -(5-Chloro-2-oxidophenyl)ethanone 4-nitrobenzoylhydrazonato(2-)] tris(pyridine)nickel(II) pyridine solvate - Basirun, Wan Jefrey; Yamin, B.M.; Ali, H.; Khamis, N.A. (International Union of Crystallography, 2004)
The double chelate ring in the title complex, [Ni(C15H 11Cl-N3O3)2]·C 5H5N, is essentially planar, with the O,N,O-donor atoms and a pyridine ligand N atom occuping the equatorial positions in a distorted octahedral environment about the Ni atom. The N-Ni-N axial bond angle is 173.16 (8)°. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.